KREATIVITAS DAN KETUNTASAN BELAJAR SISWA SMP MUHAMMADIYAH 3 SURABAYA MELALUI PENERAPAN MODEL PROJECT BASED LEARNING BERBASIS KASUS - Fikri Abdillah Syukur; Ruspeni Daesusi; Wiwi Wikanta (Universitas Muhammadiyah Surabaya, 2024)
This research aims: 1) to test the effect of the case-based PjBL model on student learning completion in an addictive substance material at SMPM 3 Surabaya; 2) to train the creativity of SMPM 3 Surabaya students in the case-based PjBL model on the addictive substance material; 3) To describe the implementation of the case-based PjBL model in learning additive substance material at SMPM 3 Surabaya; 4) To describe students' responses to the case-based PjBL model in learning addictive substance material. This type of research is pre-experimental with a One Group Pretest Posttest design. The target of the research was 16 students in class VIII of SMP Muhammadiyah 3 Surabaya. Data collection techniques used was observation, tests and questionnaires. The research results obtained: (1) The implementation of the case-based Project Based Learning model shows very good results. (2) The case-based Project Based Learning model can train students' learning creativity in the